The study of cryptographic hashing algorithms used in modern blockchain systems - Кузнецов, О.О.; Горбенко, Ю.І.; Онопрієнко, В.В.; Стельник, І.В.; Мялковський, Д.В. (Radiotekhnika, 2019)
Modern hashing algorithms that are or can be used in various blockchain systems are studied in this work. In particular, the most common and used cryptographic hashing algorithms are considered, which are standardized at the international and national levels, as well as algorithms, although not standardized, but used in most modern decentralized systems built on blockchain technology.